Hubungan Kompetensi, Pengetahuan, Motivasi dan Sumber Daya dengan Kinerja Anggota Tim Pendamping Keluarga Risiko Stunting - Anastasia Noveni; Rosihan Adhani; Ardik Lahdimawan; Meitria Syahadatina Noor; Oski Illiandri (Universitas Malahayati Lampung, 2026)
ABSTRACT The performance of the Family Assistance Team (TPK) plays a crucial role in accelerating stunting reduction, particularly in assisting families at risk of stunting. However, the implementation of TPK duties still faces various obstacles that can impact performance, including competency, knowledge, motivation, and resource availability. This study aims to analyze the relationship between competency, knowledge, motivation, and resources with the performance of TPK members at risk of stunting in Dusun Selatan District, South Barito Regency. This study used an observational analytical approach with a cross-sectional approach. The study population was all TPK members in Dusun Selatan District, South Barito Regency. The sample size was 72 individuals used a proportional random sampling technique. The independent variables were competency, knowledge, motivation, resources, and the performance of TPK members, which served as the dependent variable. Bivariate analysis used Fisher's exact test, and multivariate analysis used multiple logistic regression. The analysis demonstrated a relationship between competence (p=0.000), knowledge (p=0.000), motivation (p=0.000), and resources (p=0.000) with the performance of TPK members at risk of stunting in Dusun Selatan District, South Barito Regency. Logistic regression analysis revealed that the most dominant variable was competence (p=0.001; Exp(B) 70.357; 95% CI 5.139-963.246). Competence, knowledge, motivation, and resources significantly correlate with the performance of TPK members in South Barito Regency. It is recommended that relevant parties improve TPK performance by strengthening capacity, increasing motivation, and providing adequate resources to support effective support for families at risk of stunting. Keywords: Performance, Competence, Knowledge, Motivation, Resources, Family Support Team. ABSTRAK Kinerja Tim Pendamping Keluarga (TPK) memiliki peran penting dalam mendukung percepatan penurunan stunting, khususnya dalam pendampingan keluarga berisiko stunting. Namun, pelaksanaan tugas TPK masih menghadapi berbagai kendala yang dapat memengaruhi kinerja, di antaranya kompetensi, pengetahuan, motivasi, dan ketersediaan sumber daya. Penelitian ini bertujuan untuk menganalisis hubungan kompetensi, pengetahuan, motivasi, dan sumber daya dengan kinerja anggota TPK risiko stunting di Kecamatan Dusun Selatan Kabupaten Barito Selatan. Penelitian ini menggunakan observasional analitik dengan pendekatan cross sectional. Populasi penelitian adalah seluruh anggota TPK di Kecamatan Dusun Selatan Kabupaten Barito Selatan. Sampel penelitian ini sebanyak 72 orang dengan menggunakan teknik proporsional random sampling. Variabel bebas adalah kompetensi, pengetahuan, motivasi, sumber daya dan kinerja anggota TPK sebagai variabel terikat. Uji analisis bivariat menggunakan fisher’s exact test dan analisis multivariat menggunakan regresi logistik berganda. Hasil analisis membuktikan bahwa terdapat hubungan antara hubungan kompetensi (p=0,000), pengetahuan (p=0,000), motivasi(p=0,000), dan sumber daya (p=0,000) dengan kinerja anggota TPK risiko stunting di Kecamatan Dusun Selatan Kabupaten Barito Selatan. Analisis regresi logistik, didapat hasil variabel paling dominan adalah kompetensi (p = 0,001; Exp(B) 70,357; 95% CI 5,139-963,246). Kompetensi, pengetahuan, motivasi, dan sumber daya memiliki hubungan yang signifikan dengan kinerja anggota TPK di Kabupaten Barito Selatan. Disarankan kepada pihak terkait untuk meningkatkan kinerja TPK melalui penguatan kapasitas, peningkatan motivasi, serta pemenuhan sumber daya yang memadai guna mendukung efektivitas pendampingan keluarga berisiko stunting. Kata Kunci: Kinerja, Kompetensi, Pengetahuan, Motivasi, Sumber Daya, Tim Pendamping Keluarga.